Theoretical investigation of the equilibrium surface structure of si1-x-ygexcy alloys - Kelires, Pantelis C. (My University, 1998)
We investigate the surface structure of SiGeC alloys at typical growth temperatures using Monte Carlo simulations within the empirical potential formalism. We find a strong tendency of carbon to segregate to the top layer. As a consequence, germanium segregation is drastically reduced. The carbon composition profile oscillates in the subsurface layers, with a marked enhancement in the third layer. Si-C dimers are the favored surface bonding geometry, and are mostly found in (2 × 2) and c(4 × 2) arrangements.
Keywords: Alloys; Monte Carlo method; Segregation; Computer simulation